Early Communication Behaviors in Infants With Cleft Palate With and Without Robin Sequence: A Preliminary Study. (August 2022) - van Eeden, Stephanie; Wren, Yvonne; McKean, Cristina; Stringer, Helen
Objective: To investigate the early communication behaviors in infants with nonsyndromic isolated cleft palate (iCP) and Robin sequence (RS). Design: Group comparison using parent report. Participants: There were 106 participants included in this study. Two groups were selected from the UK Cleft Collective resource. Parents had completed the Language ENvironment Analysis Developmental Snapshot questionnaire when their child turned 13 months. There were 78 participants in the iCP group and 28 in the RS group. Main Outcome Measure(s): Total number of communication behaviors reported on the questionnaire. Subdomains for expressive and receptive language and social communication behaviors were also analyzed. Results: There were no statistically significant group differences. Parents of infants with RS reported fewer later communication behaviors compared to the iCP group. Infants in both groups had fewer communication behaviors compared to the normative sample. Across the whole sample, post hoc analysis revealed a significant correlation between severity of the cleft and social communication behaviors and expressive but not receptive language. Infants with a cleft of the hard and soft palate were more likely to be in the RS group (odds ratio: 7.04 [95% CI: 1.55-32.04]; P = .01). Conclusions: Both groups reported similar levels of early communication. Some divergence of more complex language skills was seen, although there were no significant group differences. A relationship with the diagnosis of a cleft of the hard or soft palate with expressive language behaviors was found. Further study into the impact of cleft severity on early speech development and the relationship with later language skills is needed along with longitudinal follow-up of this population.